Natural and Synthetic Efficiency of Hormones in Rooting and Development of Vegetative Structures of Tilo (Sambucos peruviana) in the High Tropics (2023)
In the high tropics, silvopastoral systems are sustainable alternatives that enhance the availability and quality  fodder for animal freeding. These agroecosystems require the spread of forage shrubby species with high productive capacity such like Tilo (Sambucos peruviana). The aim of this study,  evaluates the efficiency of three natural hormones, four synthetic hormones and a soil biofertilizer in rooting and sprout tilo´s  cuttings. A randomized complete block design was employed, with twenty-one treatments,  with three repetitions each one, determining the behavior of six variables using ANOVA, normality (Shapiro-Wilk), homogeneity of variances (Levene's) and Post-hoc (Scott-knott or Bonferroni). The results show regarding the variable denominated number of sprouts,  the highest averages were reached with T12 (cinnamon) and T11 (aloe) and H0 is accepted (P> 0.05). Meanwhile for the other five variables, a statistically significant difference was identified (P< 0.05). In sprouts weight (g.) and sprout length (cm.) the best results were obtained with T3 (Gibberellic acid); for root length (cm.) the best behavior was with T10 (mycorrhiza and canaryseed); for root weight (g.) and plant height (cm.) the highest average was with T4 (ANA+ IBA).